2010
DOI: 10.1016/j.juro.2009.08.155
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activity Measured by Functional Magnetic Resonance Imaging is Related to Patient Reported Urgency Urinary Incontinence Severity

Abstract: Purpose-To investigate the relationship between experimental neuroimaging and self-reported measures of urinary incontinence.Materials and Methods-We evaluated 14 functionally independent, community-dwelling older women (> 60 years) who had moderate to severe urgency urinary incontinence. All underwent detailed clinical assessment (3-day bladder diary, 24-hour pad test, and quality of life assessment), urodynamic testing, and functional brain scanning. Brain activity during reported urgency was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 26 publications
3
50
0
Order By: Relevance
“…In subjects who lost control of their bladder during bladder filling in the scanner, such activity amplifies (19). Regional brain activity during reported urgency in the scanner also correlates with reports of urgency incontinence on the bladder diary (17). One of the possible causes of such increased activity during urgency in older women with urinary incontinence may be due to the damage of white matter pathways that connect these centers in the brain.…”
Section: B L a D D E R S Y M P T O M S O F I D I O P A T H I C A N D mentioning
confidence: 95%
See 2 more Smart Citations
“…In subjects who lost control of their bladder during bladder filling in the scanner, such activity amplifies (19). Regional brain activity during reported urgency in the scanner also correlates with reports of urgency incontinence on the bladder diary (17). One of the possible causes of such increased activity during urgency in older women with urinary incontinence may be due to the damage of white matter pathways that connect these centers in the brain.…”
Section: B L a D D E R S Y M P T O M S O F I D I O P A T H I C A N D mentioning
confidence: 95%
“…For example, during voiding the activation of the right inferior frontal gyrus (adjacent to the dlPFC) and the medial PFC (adjacent/near to the anterior cingulate (6,7,13,16). Studies during filling of an already well-filled bladder and reported urgency also show significant activation in the dlPFC and deactivation in the ventromedial and medial part of PFC (17).…”
Section: F R O N T a L C O R T E Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a possibility of selection bias in the longitudinal data, the results demonstrate high incidence, and increasing prevalence with age of both nocturnal polyuria and nocturia. Nocturia >3 episodes per night increased from just 2.8% of men aged 50-54 up to 17.0% of men aged [70][71][72][73][74][75][76][77][78]. These data suggest also that for epidemiological purposes a definition of nocturia should be based on either two or three voids per night, with nocturnal polyuria defined as >90 ml/ hr.…”
Section: Session 31 (Poster)-nocturia and Incontinencementioning
confidence: 99%
“…However, there were no statistical differences in any outcome measure between the TOT and TVT procedures. Johnson and Latini (Abstract 218) 71 showed that urethroplasty improves lower urinary tract symptoms as measured by the American Urological Association Symptom Index with no significant effect on continence or sexual function as measured by the ISI and Sexual Health Inventory for Men. Chung et al (Abstract 220) 72 found that MRI had a 22.5% diagnostic error rate in the evaluation of urethral diverticulae.…”
Section: Session 19 (Poster)-rehabilitationmentioning
confidence: 99%